2014
DOI: 10.1016/j.oceaneng.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of armour porosity on the hydraulic stability of cube armour layers

Abstract: Armour placement and packing density directly affect construction costs and hydraulic performance of mound breakwaters. In this paper, the literature concerning the influence of armour porosity on the hydraulic stability of single-and double-layer armours is discussed.Qualitative and quantitative estimations for the influence of armour porosity and packing density on the hydraulic stability are given for the most common concrete armour units. The analysis focuses on specific 2D hydraulic stability tests of dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Given an armor unit, an armor porosity above recommended values decreases the concrete consumption but also decreases the hydraulic stability (see Medina et al, 2014), affecting the breakwater performance during lifetime.…”
Section: For Cubipod Tests Packing Densities Were Taken From Smolka mentioning
confidence: 99%
“…Given an armor unit, an armor porosity above recommended values decreases the concrete consumption but also decreases the hydraulic stability (see Medina et al, 2014), affecting the breakwater performance during lifetime.…”
Section: For Cubipod Tests Packing Densities Were Taken From Smolka mentioning
confidence: 99%
“…The specific placement technique is directly related to armor porosity (p%) and interlocking, which significantly affects armor stability. Van der Meer (1999), Yagci and Kapdasli (2003), Bakker et al (2005), and Medina et al (2014) among others, analyzed a variety of CAUs and reported a significant influence of armor porosity on hydraulic stability. Porosity is also directly related to the number of units in the armor, material consumption and hence the construction cost.…”
Section: Ii33 Techniques To Place Armor Unitsmentioning
confidence: 99%
“…Frens (2007) summarized problems caused by different researchers using different criteria regarding the layer coefficient and the porosity concept. To prevent misunderstandings, Medina et al (2014) suggested referring armor porosity p(%)=(1-Φ/n) to a layer coefficient of kΔ=1.00 using the dimensionless placing density Φ=φDn 2 . Different criteria can be used to classify armor units depending on the placement technique.…”
Section:   mentioning
confidence: 99%
See 2 more Smart Citations